Covid 19 Pandemic: The Inspiration to Start Online Business - Zaitun Zaitun; Faishal Juliyanto (BASKARA : Journal of Business and Entrepreneurship, 2022)
The pandemic of covid-19 which was announced as a disaster by President Joko Widodo on March 2, 2020 has been shaking the economic scope of Indonesia. More department stores and even big shopping centers forcibly closed due to the policy of social distancing and local lockdown. As the consequence, more people lost their jobs which worsening the economic sector. Besides this sadly fact, more people started to utilize social media to promote products. The changing of people’s behaviors who previously used to shop offline to online sites became the main reason for businesses owners to take this opportunity to keep their businesses survive. This new life style also inspired many people to start online trades to earn their livings. The objective of this descriptive paper was to present how one of English students of Faculty of Education, Muhammadiyah University of Jakarta, who joined entrepreneur class was being inspired by the situation of covid-19 to start online business. This study used both observation and unstructured interview as the tools in collecting the data. The results of the study presented three answers of the research questions, namely: first, the student was inspired by the rapid spreading of online business and most business owners who promoted various products online. Second, in the preparation, he determined a label as his virtual store name, designing logo, creating ‘thank you’ card and buying good quality materials with low prices for the packaging. Third, after the first three months becoming reseller of women’s stuffs such as body treatment, bags, shoes, cosmetics and various accessories, up to end of September, more than hundred goods had been sold and he could earn around one million of net-profit every month. Even more, currently, he has been saving money as the capital, stocking quite big number of stuffs and planning to have one physical store to run the business offline after the pandemic is over.